Psychometric validation of an organizational citizenship scale in Colombian university teachers - Mabel Ibarra Luna; Pablo Erazo-Muñoz; Braian López Ossa (Institute of Advanced Engineering and Science, 2026)
Many assessment scales used to study organizational citizenship behavior (OCB) in Latin American countries are adaptations of instruments developed in other cultural settings. In this regard, the objective of this study was to evaluate the structural validity and reliability of the organizational citizenship behavior scale for coworkers (ECCOCT) in Colombian university teachers. An exploratory factor analysis (EFA) with principal axis extraction and Oblimin rotation was used, followed by a confirmatory factor analysis (CFA) with robust maximum likelihood (MLR). Omega, average variance extracted (AVE), and heterotrait–monotrait ratio (HTMT) were calculated. Participants included 113 university teachers from the city of Manizales, Colombia. The EFA showed that of the five dimensions proposed by the theory, two accurately reflect OCB (OCB directed toward individuals (OCB-I) and OCB directed toward the organization (OCB-O)), explaining 64.2% of the variance. The two-dimensional model showed an excellent fit (χ²/gl=1.24; comparative fit index (CFI)=.977; root mean square error of approximation (RMSEA)=.046). The reliability of the factors was ω=.90 and ω=.84. Convergent validity (AVE>.50) and discriminant validity (HTMT<.85) were corroborated. The ECCOCT in its two dimensions shows solid psychometric properties and constitutes a brief and valid instrument for assessing organizational citizenship in Latin American contexts.